Adsorption of congo red using kaolinite-cellulose adsorbent - Santa Oktavia Ginting; Risfidian Mohadi (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2017)
Kaolinite was impregnated with cellulose extracted from rubber wood fibers has been done. The product of impregnated kaolinite-cellulose was characterized using FT-IR spectrophotometer. Furthermore, the impregnation results are used as an adsorbent of Congo red. Adsorption of Congo red was also studied the kinetic and thermodynamic parameters. The results of characterization using FT-IR spectrophotometer shows the process of impregnation was successfully conducted. It was indicated that the presence wavenumber at 910.4 - 918.12 cm-1 and 1033.85 cm-1 become 1026.13 cm-1 and the existence of vibration at wavenumber 2931.8 cm-1. The pH of adsorption was adjusted to 4 before the adsorption process. The adsorption process of cellulose impregnated kaolinite shows the rate of adsorption (k) of 0.002 min-1, the adsorption reviews largest capacity (b) at 50 °C was 500 mol/g. The greatest adsorption energy (E) at 40 °C is 11:09 kJ/mol. The enthalpy value (ΔH) and entropy (ΔS) decreased with increasing Congo red dye concentration. Keywords: kaolinite, cellulose, impregnation, Congo red